Political Parties in Africa : challenges for sustained multiparty democracy : Africa regional report based on research and dialogue with political parties - Salih, Mohamed Abdel Rahim M. (Mohamed Abdel Rahim Mohamed); Nordlund, Per.; International Institute for Democracy and Electoral Assistance (Stockholm : International Institute for Democracy and Electoral Assistance, 2007)
Provides a broad, comparative analysis of 27 African countries and 75 political parties. The data was assembled during 2004-06 and was followed by national and sub-regional dialogue workshops between political parties, researchers and civil society. The agenda for reform that emanated from the research and dialogue process is reflected and discussed in the report. Legislative regulation of parties, women's participation, funding of political parties, party democracy and party programmes and policies that represent and reflect the preferences of the people are high on the agenda for the process ahead. By providing comparative information, this International IDEA publication aims to stimulate debate on the challenges faced by political parties in Africa. It is especially aimed at political parties, scholars, policy makers and democracy assistance organizations working for political reform in Africa.
Viewed on (Mar. 16, 2007).
Lead authors: M.A. Mohamed Salih and Per Nordlund.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Keywords: Political parties -- Africa